Product simplification design improvement by using DFMA method - Tan, Ni Yen (2012)
objective of this project is to propose a new design for price labeler. Apart from that, the manufacturing cost, assembly cost and time are also analysed to support the improvement. The analysed were carried out through dismantle a unit of product, functioning of each component and 3D modelling using SolidWork software and lastly is using DFMA design guidelines to generate a new design. The selection criteria for a good design are based on manufacturing cost and assembly time. Finally, the chosen design was proven meet all needed criteria by improving 16.29% of the design efficiency. The existing product design efficiency is 26.62% and the new propose of design is 41.26%. The labour cost also manages to reduce RM0.1940 per product. For the Design for Manufacturing (DFM) part, the better manufacturing process chooses is injection moulding and the material used is Thermoplastic. Since the material choose is Thermoplastic, so will maintain the original material which is Acrylonitrile butadiene styrene (ABS). In this study, the overall cost reduction for DFMA is RM0.19 per product which is RM1.50 reduce to RM1.31, the percentage reduction is 12.67%.